THE ROLE OF PACKAGING TECHNOLOGY IN LIBRARY PRESERVATION: BEST STORAGE PRACTICES AT THE NATIONAL LIBRARY OF HUNGARY (Bulletin of Armenian Libraries, 2025)
Since the foundation of the National Széchényi Library (NSZL), it has served as a repository of knowledge and a custodian of Hungarian cultural heritage, making paper-based and electronic library documents publicly accessible. Therefore, it is library's duty to preserve its collection in the best way possible for future generations. The library has adopted a new sustainable practice to protect cultural heritage objects housed in the national library. In this paper the author will discuss their approach to preserving analogue documents.